The Periodontal Status in Pregnant Women - H. Hecová; Z. Broukal; V. Merglová; J. Stehlíková; P. Chaloupka (Czech Dental Chamber, 2013)
Introduction: The presence of periodontal pathogens in microbial plaque in pregnant women can act as a risk factor increasing the possibility of adverse pregnancy outcomes. Aims: The aim of this study was to investigate periodontal status of pregnant women in the third trimester and to compare the findings in women with physiologic and risk pregnancy. Materials and methods: The study included 61 women with a physiological pregnancy (group F) and 81 women with a risk pregnancy (group R). The age of women in both groups ranged from 21 to 41 years. The CPI and PBI indices have been recorded in all pregnant women and microbial testing for five basic periodontal pathogens (Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola, and Prevotella intermedia) was performed in 19 women.Statistical processing the data: Mann-Whitney test, Pearson's χ2 test (p < 0.05). Results: The study results showed that the total CPI score did not differed between F and R groups, but women with a risk pregnancy had significantly higher PBI score that those with physiologic pregnancy (p = 0.019) and significantly higher mean count of sextants with CPI = 3-4 (p = 0.032). The need of hygienic briefing and periodontal treatment (CPI≥1) was found totally in 141 women [60 women (98%) with a physiological pregnancy and 81 women (100%) with risk pregnancy]. Two women among 19 microbiologically screened showed the high or extremely high levels of four periodontal pathogens with Tannerella forsythia being the most frequently detected (≥105). Preterm labour and low birth weight of children appeared in three women of 19 screened for periodontal pathogens (in two with periodontal pathogens level exceeding 105 and one with non-detectable levels). Conclusion: The study has confirmed the need of increased attention to periodontal tissues and oral hygiene during preventive dental appointments in pregnant women.